DIPLOMASI PEMERINTAHAN SUSILO BAMBANG YUDHOYONO MENANGANI KASUS TERPIDANA MATI TKI DI MALAYSIA (2004-2014) DIPLOMACY OF SUSILO BAMBANG YUDHOYONO GOVERNMENT TO HANDLE THE CASE OF DEATH PINALTY TO IND - Eri Prasetyo Mahanani (HI 16 UMY 012, 2016)
*12 The research of Diplomacy of Susilo Bambang Yudhoyono Goverment To Handling The Case Of Death Penalty to Indonesian Workers In Malaysia. This type of research used in this research is literature study (library research), the method of research that is based from books, journals, and other written sources of useful and supports research.